Hydraulic accumulators in energy efficient circuits - Costa, Gustavo Koury; Sepehri, Nariman (Frontiers in Mechanical Engineering, 2023)
Hydraulic accumulators have long been used in hydraulic circuits. Applications vary from keeping the pressure within a circuit branch to saving load energy. Amongst these applications, storing and releasing energy has gained attention in recent years due to the need for efficient circuits. In this sense, accumulators are the hydraulic counterparts of batteries and capacitors in electrical circuits. From hydraulic hybrid vehicles to complex agricultural machinery, accumulators have been successfully implemented and significant energetic gains have been reported. This paper reviews typical applications where accumulators can be used to this end and discusses the challenges that still need to be overcome in each situation.